Antibiotic treatment reduces fecundity and nutrient content in females of Anastrepha fraterculus (Diptera: Tephritidae) in a diet dependent way - Goane, Lucía (2022)
Insect microbiota, particularly, gut bacteria has recently gained especial attention in Tephritidae fruit flies, being Enterobacteriaceae the predominant bacterial group. This bacterial group has been postulated to contribute to the fitness of fruit flies through several life-history traits. Particularly in Anastrepha fraterculus, removal of Enterobacteria from male gut via antibiotic treatment impaired their mating behavior. Because the impact of gut bacteria on female reproduction was not yet addressed, we here analysed the effect of antibiotic treatment on female fecundity and nutritional status, and further explored the role of bacteria under different dietary regimes. The removal of culturable Enterobacteria from the gut of females was associated to a reduction in fecundity as well as in the protein and lipid reserves. However, fecundity reduction depended on the dietary regime; being more pronounced when females fed a poor diet. Our results suggest that nutrient reserves of females are determined, at least to some extent, by intestinal bacteria (particularly Enterobacteria). The effect of antibiotics on fecundity could be explained, thus, as a consequence of a poorer nutritional status in antibiotic-treated females compared to control females. Our results contribute to understand the interaction between gut bacteria and Tephritidae fruit flies. Considering the relevance of this insect as fruit pest and the widespread use of the sterile insect technique to control them, these findings may lead to practical applications, such as development of efficient mass rearing protocols of A. fraterculus that supplement the adult diet with probiotics.